2021
DOI: 10.1002/jclp.23187
|View full text |Cite
|
Sign up to set email alerts
|

Is perfectionism always unhealthy? Examining the moderating effects of psychological flexibility and self‐compassion

Abstract: Objective: Perfectionism is generally associated with worse mental health outcomes, though evidence suggests elements of it may be helpful. In light of these findings, we examined whether psychological skills like psychological flexibility and self-compassion moderated the relationship between perfectionism and wellbeing (i.e., quality of life, symptom impairment, and psychological distress).Methods: Undergraduate students (N = 677) completed self-report measures.Results: A latent profile analysis identified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…This finding supports our hypothesis and extends previous studies that found that self-compassion a enuates self-criticism [26,31] and the negative reactions (such as a sense of failure and humiliation) to unpleasant life events [51]. Therefore, selfcompassion is a psychological resource that should cultivated especially in individuals with high levels of maladaptive perfectionism [52,53].…”
Section: Discussionsupporting
confidence: 91%
“…This finding supports our hypothesis and extends previous studies that found that self-compassion a enuates self-criticism [26,31] and the negative reactions (such as a sense of failure and humiliation) to unpleasant life events [51]. Therefore, selfcompassion is a psychological resource that should cultivated especially in individuals with high levels of maladaptive perfectionism [52,53].…”
Section: Discussionsupporting
confidence: 91%
“…In fact, existing literature supports this interpretation. The two studies that looked at the relationship between maladaptive perfectionism and depression found the protective effect of self-compassion (Abdollahi et al, 2020;Ferrari et al, 2018), yet the one that looked at perfectionism and psychological distress (depression and anxiety symptoms combined) did not (Ong et al, 2021). With adaptive perfectionism controlled for, the current study further informs future research that self-compassion might have unique moderating effects on maladaptive perfectionism's relationships with depression and anxiety respectively.…”
Section: Distressmentioning
confidence: 52%
“…Be aware of these internal states, particularly recognizing the hypercritical judgment towards oneself, which allows people to change their attitude and treat themselves with benevolence and understanding (e.g., being kind to yourself even when you cannot reach your best). Therefore, self-compassion is a psychological resource that should be cultivated, especially in individuals with high levels of maladaptive perfectionism [35,55].…”
Section: Discussionmentioning
confidence: 99%